Correlation between atomic spacing and magnetic behaviour in Ce binary compounds - Sereni, Julian Gustavo R. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Sereni, Julian Gustavo R. Comisión Nacional de Energía Atómica; Argentina